Worldwide incidence of surgical site infections in general surgical patients: A systematic review and meta-analysis of 488, 594 patients. (November 2021) - Gillespie, Brigid M.; Harbeck, Emma; Rattray, Megan; Liang, Rhea; Walker, Rachel; Latimer, Sharon; Thalib, Lukman; Erichsen Andersson, Annette; Griffin, Bronwyn; Ware, Robert; Chaboyer, Wendy
Abstract: Background: Establishing worldwide incidence of general surgical site infections (SSI) is imperative to understand the extent of the condition to assist decision-makers to improve the planning and delivery of surgical care. This systematic review and meta-analysis aimed to estimate the worldwide incidence of SSI and identify associated factors in adult general surgical patients. Materials and methods: A systematic review was undertaken using MEDLINE (Ovid), CINAHL (EBSCO), EMBASE (Elsevier) and the Cochrane Library to identify cross-sectional, cohort and observational studies reporting SSI incidence or prevalence. Studies of less than 50 participants were excluded. Data extraction and quality appraisal were undertaken independently by two review authors. The primary outcome was cumulative incidence of SSI occurring up to 30 days postoperative. The secondary outcome was the severity/depth of SSI. The I 2 statistic was used to explore heterogeneity. Random effects models were used in the presence of substantial heterogeneity. Subgroup, meta-regression sensitivity analyses were used to explore the sources of heterogeneity. Publication bias was assessed using Hunter's plots and Egger's regression test. Results: Of 2091 publications retrieved, 62 studies were included. Of these, 57 were included in the meta-analysis across six anatomical locations with 488, 594 patients. The pooled 30-day cumulative incidence of SSI was 11% (95% CI 10%–13%). No prevalence data were identified. SSI rates varied across anatomical location, surgical approach, and priority (i.e., planned, emergency). Multivariable meta-regression showed SSI is significantly associated with duration of surgery (estimate 1.01, 95% CI 1.00–1.02, P = .014). Conclusions: and Relevance: 11 out of 100 general surgical patients are likely to develop an infection 30 days after surgery. Given the imperative to reduce the burden of harm caused by SSI, high-quality studies are warranted to better understand the patient and related risk factors associated with SSI.